Negative Differential Resistance Behavior in Delta-Doped AlInP Structure Grown by MOCVD - K. F. Yarn (Active and Passive Electronic Components)
An AlInP delta-doped schottky diode exhibiting negative differential resistance (NDR) behavior is demonstrated for the first time. The NDR characteristics with a peak to valley ratio of 5.5 and peak current density of 1KA/cm2 were achieved at room temperature. In addition, the maximum available power is estimated up to 5W/cm2 . The mechanism for such performance is phenomenologically analyzed by the combination of resonant interband tunneling (RIT) and thermionic emission processes associated with tunneling effect on the metal-semiconductor (MS) interface.